Crystalline-state reaction with allosteric effect in spin-crossover, interpenetrated networks with magnetic and optical bistability. - Niel, V; Thompson, A; Muñoz, M; Galet, A; Goeta, A; Real, J (2003)
A net change: A fully reversible ligand substitution involving coordination/ uncoordination of gaseous water and pyrimidine induces the repetitive allosteric transformation of three interpenetrated nets into a single three-dimensional net. The transformation does not affect the crystallinity of the sample but alters significantly the spin-crossover transition; the compound shows magnetic and chromatic bistability (see picture).